Natural occurrence of Beauveira bassiana (Balsamo) Vuill. in Aracanthus sp. (Coleoptera: Curculionidae) in common bean - Maurício Ursi Ventura; Dáfi la Fagotti; Aline Pissinati; Adriana Yatie Mikami (Biotemas, 2009)
We investigated the natural occurrence of the entomopathogenic fungus Beauveria bassiana in a population of Aracanthus sp. in common a bean field in Londrina, PR. Four samples were taken with six repetitions each. The dead insects were monitored for infection of fungi (every 3 days for a period of 15 days). Among the dead insects it was shown that 72, 63, 84 and 79% respectively in each sample were infected by the fungus, indicating that this is a potential agent for the control of Aracanthus sp.